The Relationship of Digital Transformation and Value Architecture Towards Business Performance in Manufacturing Industry - Ahmad, Md Fauzi; Abdullah, Huda; Ahmad, Ahmad Nur Aizat; Chan, Shiau Wei; Abdul Hamid, Nurhadilah; Shahron, Syairah Aimi (UUM Press, 2025)
The digital economy has become a pivotal force driving nations towards enhanced competitiveness and customer value delivery, with Malaysia being no exception. Despite this imperative, the pace of digital adoption within Malaysian businesses trails considerably behind the global average. This research endeavoursto elucidate the intricate relationship between digital transformation, value architecture, and business performance. Employing a quantitative methodology and random sampling technique, data was gathered through a survey questionnaire administered to 150 respondents from the manufacturing sector. Results revealed significant correlations between digital transformation, value architecture, and business performance. Notably, the manufacturing subsector emerges as a significant influencer on both digital transformation and business performance. These findings underscore the widespread acceptance of digital transformation and value architecture within the manufacturing industry as indispensable tools for augmenting business performance. Consequently, the manufacturing sector assumes a pivotal role in driving economic growth and societal advancement, characterized by employment expansion and export stimulation. Moreover, this study advocates for enhanced operational efficiency, aligning with Malaysia’s strategic initiative, My Digital, aimed at catapulting the nation into a high-income, digitally-driven economy